Vibrational spectra, thermodynamic functions and barriers to internal rotation for isomeric trifluoromethylbenzoyl chlorides - Shanker R.; Yadav R.A.; Singh I.S.; Singh O.N. (My University, 2025)
The polarized Raman spectra (50–4000 cm−1) and IR spectra (180–4000 cm−1) of o‐, m‐ and p‐ trifluoromethylbenzoyl chlorides were recorded and all the 45 (30a′ + 15a") normal modes of vibration were assigned assuming Cs symmetry. Consistent assignments for the internal modes of the COCl and CF3 groups are proposed. Thermodynamic functions were computed and barriers to internal rotations for the COCl and CF3 tops were determined, using the assigned vibrational frequencies and assumed structural parameters for the three isomers. Copyright © 1992 John Wiley & Sons, Ltd.